2019
DOI: 10.1074/jbc.ra119.009409
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 transcription factor regulates chondrogenic differentiation through transforming growth factor β1 signaling

Abstract: The forkhead box O (FOXO) proteins are transcription factors involved in the differentiation of many cell types. Type II collagen (Col2) Cre-Foxo1-knockout and Col2-Cre-Foxo1,3,4 triple-knockout mice exhibit growth plate malformation. Moreover, recent studies have reported that in some cells, the expressions and activities of FOXOs are promoted by transforming growth factor β1 (TGFβ1), a growth factor playing a key role in chondrogenic differentiation. Here, using a murine chondrogenic cell line (ATDC5), mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…In our experiments investigating whether FoxO1/3 inhibitor AS1842856 would restore SOX9 levels in the presence of EtOH, we found 1 μ M AS1842856 completely inhibited chondrogenic differentiation. Indeed, a recent study showed that FoxO1 is required for SOX9 expression (Kurakazu et al, 2019). We found that a 10‐fold decrease in AS1842856 permitted chondrogenic differentiation, but did not fully restore SOX9 expression in EtOH‐exposed MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments investigating whether FoxO1/3 inhibitor AS1842856 would restore SOX9 levels in the presence of EtOH, we found 1 μ M AS1842856 completely inhibited chondrogenic differentiation. Indeed, a recent study showed that FoxO1 is required for SOX9 expression (Kurakazu et al, 2019). We found that a 10‐fold decrease in AS1842856 permitted chondrogenic differentiation, but did not fully restore SOX9 expression in EtOH‐exposed MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…More likely, FoxO1/3 activity may be required, in at least at some basal level of activity, for osteogenic and chondrogenic differentiation. Indeed, several studies show that FoxO1/3, as well as endogenous ROS, is required for both osteogenic and chondrogenic differentiation and normal bone turnover (Alund et al, 2016; Kurakazu et al, 2019; Teixeira et al, 2010). Presently, our findings suggest the overexpression of FoxO1/3 is responsible for the inhibition of osteogenesis and chondrogenesis in EtOH‐exposed MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…3A and B ). Finally, in chondrogenic media, BMP2 induced chondrogenic differentiation of 5-aza-CN-treated NIH-3T3 fibroblasts, which significantly increased the expression of chondrogenic markers such as aggrecan (ACAN) and type II collagen (COL2) which are major matrix proteins of cartilaginous tissue, and SRY-box 9 (SOX9) which is essential transcription factor for differentiation of precursors cells into chondrocyte [ 25 ], as well as proteoglycan stained by Alcian blue was significantly increased ( Fig. 3C and D ).…”
Section: Resultsmentioning
confidence: 99%
“…Some cytokines, such as TGF-β1, can induce MSC chondrogenic differentiation [ 58 ]. Research by Agata Zykwinska confirms that microcarriers based on marine exopolysaccharide (EPS) can encapsulate TGF-β1, which has potential in future applications for repairing cartilage defects [ 59 ].…”
Section: Overview Of the Advantages Of Microcarriers In The Treatmentmentioning
confidence: 99%